Relationship between relative age, anthropometry, maturity and motor skills in young alpine ski racers compared to pupils of the same age - Müller, L.; Hildebrandt, C.; Raschner, C. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: A relative age effect (RAE) consists of an over-representation of athletes born early in a selection year. It was shown to be present in ski racing at all age categories (Muller et al., 2012). The causal mechanisms for its existence still remain unclear; due to the high demands of physical abilities in ski racing, the consideration of the influence of biological maturation on the RAE seems to be important. Methods: 139 pupils (10-14 years) were investigated; 53 (31m, 22f) of them of a ski boarding school and 86 (46m, 40f) of a secondary modern school of the same region (a new approach in RAE research, to include a comparison group of non-athletes). Anthropometric measurements, 6 physical performance tests and the estimation of the maturity status and consequently the calculation of the age at peak height velocity (A-PHV) (Malina et al., 2012) were carried out and the birth months (divided into four quarters) were examined. ANOVA was used to evaluate differences in anthropometrics, physical performance and A-PHV between the pupils born in the single relative age (RA) quarters. Correlations between the physical performance and the A-PHV were assessed. Significance was set at p<0.05. Results: The ski racers born in the four quarters did not differ in anthropometrics and physical performance; however, they differed significantly (p=0.02; F=3.59) in the A-PHV with lower values for relatively older athletes. The pupils of the control group did not differ in any variable. The ski racers were highly significant better in all physical performance tests. A significant correlation was shown between the A-PHV and the agility test (p<0.001; r=-0.45), the core strength test (p=0.036; r=0.3) and the counter movement jump (p=0.049; r=0.27) within the group of the ski racers and between the A-PHV and the core strength test (p=0.005; r=0.3) and the drop jump (p=0.047; r=-0.22) within the comparison group. Discussion: The ski racers born in the four quarters differed significantly in the A-PHV with lower values for relative older athletes, which means that they are more mature and accelerated compared to the relatively younger ski racers. This is in line with studies for example in soccer, where the maturity status significantly correlated with RA. Interestingly, this was not shown for the comparison group, which indicates that biological maturation correlates with the RA only in alpine ski racers. The superiority of the ski racers in physical performance underlines the importance of these skills in ski racing.